18F-FDG PET/CT detection of primary mammary-like adenocarcinoma of the vulva with multiple metastases: a case report - Song, Qing; Gu, Yu (Frontiers in Oncology, 2024)
Mammary-like adenocarcinoma of the vulva is a malignancy with a low incidence rate compared with the squamous cell carcinoma occurring at the same site. We present a rare case of mammary-like adenocarcinoma of the vulva with multiple-organ involvement using 18F-FDG PET/CT. This study indicates that 18F-FDG PET/CT can not only detect the primary lesion but also distinguish the stage of the mammary-like adenocarcinoma of the vulva.